APRIMORAMENTO DE UM MANIPULADOR ROBÓTICO ACIONADO PNEUMATICAMENTE - Locateli, Cristiano C.; Zago, Fernando; Schmitt, Paulo R.; Valdiero, Antonio C.; Andrighetto, Pedro L.; Endler, Luciano (Salão do Conhecimento, 2013)
Resumo